Workplace Safety: A Necessity or a Luxury in the Micro, Small and Medium Enterprises of Bangladesh? - Al Amin , Mohammed Nafeez (American Journal of Trade and Policy, 2016)
Following the deadliest accidental structural failure in modern human history, Bangladesh Government has been getting external pressure to amend and properly implement its “Workplace Safety Laws”. Garment factories like the ones in Rana Plaza (the collapsed building in Savar) are large organizations. Along with the large companies, there are a significant number of micro, small and medium-sized enterprises in Bangladesh which are employing more than 31 million people. Obviously, workplace safety should be a matter of concern for their employers, or is it? Why are they reluctant about it? What is being done to ensure safety? Are they getting pressures or motivated by externalities? Safety measures if taken, is it enough? What else can be done to improve workplace safety? The purpose of this research paper is to find out and analyze the answers to the above questions concerning workplace safety in the MSMEs of Bangladesh. A blend of secondary sources and primary sources (survey amongst a significant number of owners of various MSMEs and observation of a few organizations) of data were used from which both quantitative and qualitative analyses were carried out for the purpose of exploring the unknown. The results show a rather reluctant approach by the owners regarding this issue. However, it was also found that the government has taken a lot of initiatives to minimize workplace safety hazards and is on the verge of implementing them. Thus, a few alternatives that involve lobbying and use of marketing activities to create greater awareness were recommended. JEL Classifications Code: J81, J88